ACCOUNTING TREATMENT OF REVENUE ALL-INCLUSIVE PACKAGEAT HOTEL GB - Dina Maria Fransisca; Wayan Tuwi; I Gusti Ngurah Agung Wiryanata (RADJA PUBLIKA, 2025)
The growing interest in all-inclusive packages among tourists requires a comprehensive understanding of the accounting treatment applied to the resulting revenue, especially when multiple service departments are involved in a single transaction. This study aims to analyze the recognition, measurement, presentation, and disclosure of revenue from all-inclusive packages at the GB hotel in accordance with PSAK No. 72. Employing a qualitative descriptive method, the research utilized primary and secondary data collected through interviews, observations, and documentation, followed by data reduction, presentation, and conclusion drawing based on the PSAK framework. The findings reveal that revenue recognition is carried out using the accrual basis after the fulfillment of performance obligations, while measurement is based on the actual price of services allocated proportionally to each department involved. Presentation is performed by separating revenue into room, food & beverage, and spa categories in the income statement, and disclosure is provided in detail per department in the notes to the financial statements. These results indicate that GB hotel has effectively implemented accounting practices aligned with PSAK No. 72, ensuring transparency, compliance, and accuracy in revenue reporting for all-inclusive packages